Selective accumulation of biotin in arterial chemoreceptors: requirement for carotid body exocytotic dopamine secretion - Ortega‐Sáenz, Patricia (J Physiol, 2016)
KEY POINTS: Biotin, a vitamin whose main role is as a coenzyme for carboxylases, accumulates at unusually large amounts within cells of the carotid body (CB). In biotin‐deficient rats biotin rapidly disappears from the blood; however, it remains at relatively high levels in CB glomus cells. The CB contains high levels of mRNA for SLC5a6, a biotin transporter, and SLC19a3, a thiamine transporter regulated by biotin. Animals with biotin deficiency exhibit pronounced metabolic lactic acidosis. Remarkably, glomus cells from these animals have normal electrical and neurochemical properties. However, they show a marked decrease in the size of quantal dopaminergic secretory events. Inhibitors of the vesicular monoamine transporter 2 (VMAT2) mimic the effect of biotin deficiency. In biotin‐deficient animals, VMAT2 protein expression decreases in parallel with biotin depletion in CB cells. These data suggest that dopamine transport and/or storage in small secretory granules in glomus cells depend on biotin. ABSTRACT: Biotin is a water‐soluble vitamin required for the function of carboxylases as well as for the regulation of gene expression. Here, we report that biotin accumulates in unusually large amounts in cells of arterial chemoreceptors, carotid body (CB) and adrenal medulla (AM). We show in a biotin‐deficient rat model that the vitamin rapidly disappears from the blood and other tissues (including the AM), while remaining at relatively high levels in the CB. We have also observed that, in comparison with other peripheral neural tissues, CB cells contain high levels of SLC5a6, a biotin transporter, and SLC19a3, a thiamine transporter regulated by biotin. Biotin‐deficient rats show a syndrome characterized by marked weight loss, metabolic lactic acidosis, aciduria and accelerated breathing with normal responsiveness to hypoxia. Remarkably, CB cells from biotin‐deficient animals have normal electrophysiological and neurochemical (ATP levels and catecholamine synthesis) properties; however, they exhibit a marked decrease in the size of quantal catecholaminergic secretory events, which is not seen in AM cells. A similar differential secretory dysfunction is observed in CB cells treated with tetrabenazine, a selective inhibitor of the vesicular monoamine transporter 2 (VMAT2). VMAT2 is highly expressed in glomus cells (in comparison with VMAT1), and in biotin‐deficient animals VMAT2 protein expression decreases in parallel with the decrease of biotin accumulated in CB cells. These data suggest that biotin has an essential role in the homeostasis of dopaminergic transmission modulating the transport and/or storage of transmitters within small secretory granules in glomus cells.